PENGEMBANGAN, VALIDASI, DAN APLIKASI SKALA SIKAP SISWA TERHADAP PELAJARAN KIMIA BERORIENTASI KEJURUAN - Pujiani, Sri (2017)
Penelitianinibertujuanmengembangkaninstrumenskalasikapterhadappelajarankimia yang berorientasikejuruan, menguji validitasnya serta mengaplikasikannya untuk memperoleh profil sikap siswa terhadap pelajaran kimia.Skala sikap ini hasil modifikasi dari Attitude Toward Chemistry Lesson Scale (ATCLS) oleh Derek Cheung, berbentukskala Likert tujuhpoindengan 25 butirpernyataanpadaempatdimensisikap. Skalasikapinidikembangkanmelaluipengujianvaliditasisidenganpertimbangan para ahlidanvaliditaskontrukdengananalisisfaktoreksploratori.Subjekpenelitianadalahsiswa SMK kelas X, XI, dan XII denganpaketkeahlianFarmasidan Kimia Analisis. Pengujianreliabilitasskalasikapdilakukanterhadap 155 siswamenghasilkannilai Alpha Cronbach sebesar0,896dengankategoriBaik.Aplikasiskalasikapinimenghasilkanprofilsikap 300 siswaterhadappelajarankimiadengan rata-rata sikappadadimensisikap: Kesenanganterhadap Kimia kategoriRendah (4,54), KeyakinanBelajar Kimia kategori Tinggi (5,66), KesenanganBereksperimen Kimia kategoriMenengah (5,19), danKecemasanBelajar Kimia kategoriMenengah (5,19).Padapenelitianini, faktor-faktor yang mempengaruhisikapsiswaterhadappelajarankimiaadalahperbedaanpaketkeahliandankelas. Kata kunci: SikapterhadapPelajaran Kimia,SkalaSikap, Validitas,Reliabilitas, This study aims to develop an attitude scale instrument towards vocational-oriented chemistry lessons, examine its validity and apply it to obtain students' attitude profile towards chemistry lessons. This attitude scale is modified from the Attitude Toward Chemistry Lesson Scale (ATCLS) by Derek Cheung, a seven point Likert scale with 25 item statements on four dimensions of attitudes. This attitude scale was developed through both content validity test by using expert judgement and construct validity test by using exploratory factor analysis. Subjects in this study are students of SMK for class X, XI, and XII who majoring in Pharmaceutical and Chemistry Analysis. Attitude scale reliability test was administered to 155 students resulted in Alpha Cronbach value of 0.896 with Good categories. Application of this attitude scale is performed to determine profile of students' attitudetowards chemistry lessons of 300 students resulted in average attitude for each attitudes dimension: Liking for Chemistry Theory Lessons with Low categories (4,54), Confidence in Chemistry Learningwith High categories (5,66), Liking for Chemistry Laboratory Works with Moderate categories (5,19), and Anxiety of Chemistry Learningwith Moderate categories (5,19). In this study, the factors that influence students' attitudes toward the chemistry lessons are differencesin competency skills and grade levels. Keywords: Attitudetowards Chemistry Lesson, Attitude Scale, Validity, Reliability